2019
DOI: 10.1532/hsf.2419
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Randomized and Observational Studies: Aspirin Protects from Cardiac Surgery-Associated Acute Kidney Injury

Abstract: Background: Antiplatelet therapy is critical in the management of coronary artery diseases. For patients undergoing cardiac surgeries, including coronary artery bypass graft (CABG) and valve replacement, controversy remains in preoperative antiplatelet therapy concerning risk of bleeding. For safety concern, aspirin is recommended to be withdrawn 5 to 10 days before a cardiac surgery. Recent studies, however, indicate that preoperative aspirin may have a protective effect on cardiac surgery-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…Recent studies have reported the impact of commonly used medications on AKI after cardiac surgery. A meta‐analysis 24 revealed that low‐dose aspirin has a protective effect on AKI after cardiac surgery without increasing the risk of bleeding. Additionally, several studies have shown that preoperative use of ACE inhibitor/ARB is associated with a higher risk of AKI postoperatively, and discontinuing these medications before cardiac surgery may reduce the incidence of AKI 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the impact of commonly used medications on AKI after cardiac surgery. A meta‐analysis 24 revealed that low‐dose aspirin has a protective effect on AKI after cardiac surgery without increasing the risk of bleeding. Additionally, several studies have shown that preoperative use of ACE inhibitor/ARB is associated with a higher risk of AKI postoperatively, and discontinuing these medications before cardiac surgery may reduce the incidence of AKI 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the amount of patients with AKI stage 2-3 in the aspirin group were fewer than that in the non-aspirin group (stage 2-3: 76.8% VS 80.4%), suggesting that aspirin did not exacerbate AKI. Rather, aspirin may improve renal perfusion through inhibiting thromboxane, antiplatelet aggregation, and reducing microembolism [18], and it has been demonstrated to reduce the risk of postoperative CSA-AKI and mortality in cardiac surgery patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aspirin was found to alleviate proteinuria, hematuria, and improve renal function in the patients with progressive IgA nephropathy [11]. Aspirin intervention before cardiac surgery have been demonstrated to reduce cardiac surgery-associated acute kidney injury (CSA-AKI), major adverse cardiac, and cerebral events (MACE) with a reduced mortality [12][13][14]. However, aspirin intervention may increase the risk of major bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of non-ASA NSAIDs for cardiac surgical patients has been associated with acute kidney injury, 89 whereas ASA use has been shown to be protective. 90 Acetaminophen or paracetamol is a known cyclooxygenase (COX) inhibitor, although it does not exert its effect through peripheral inhibition of this enzyme as the non-steroid anti-inflammatory class of medications. 91 There is evidence that it inhibits COX centrally and acts through other non-COX mechanisms as well.…”
Section: Management Of Pppmentioning
confidence: 99%
“…Furthermore, the use of non-ASA NSAIDs for cardiac surgical patients has been associated with acute kidney injury, 89 whereas ASA use has been shown to be protective. 90 …”
Section: Management Of Pppmentioning
confidence: 99%